THE PROBLEM OF CIVIL IDENTITY FORMATION OF JUNIOR SCHOOLCHILDREN IN THE LESSONS OF THE PHILOLOGICAL CYCLE IN THE ASPECT OF LEGAL CONSCIOUSNESS DEVELOPMENT - Микерова, Галина; Кравченко, Любовь (SWorldJournal, 2020)
The article deals with the problem of the formation of civic identity of primary schoolchildren in the aspect of the development of legal consciousness through the lessons of the philological cycle. For this purpose, an experimental work was carried out t